Clinical trials of vitamin B6 and proline supplementation for gyrate atrophy of the choroid and retina. Issue 4 (April 1985) - Hayasaka, S.; Saito, T.; Nakajima, H.; Takahashi, O.; Mizuno, K.; Tada, K.
Abstract : Five patients with gyrate atrophy of the choroid and retina were examined ophthalmologically, especially ophthalmoscopically, to evaluate trials of vitamin B6 (pyridoxine) or supplementary proline. The oral administration of vitamin B6 was tried in two patients. The vitamin did not alter the serum ornithine level and the progression of chorioretinal atrophy in one patient (case 2). Despite a reduced serum ornithine level following vitamin B6 administration, chorioretinal atrophy progressed gradually in another patient (case 3). Supplementary proline was tried in four patients. Despite the supplementation the serum proline level did not increase, and the chorioretinal atrophy progressed in one patient (case 2) who received both vitamin B6 and proline. Supplementary proline minimised the progression of gyrate atrophy in the youngest patient (case 1) and halted the progression in two others (cases 4 and 5). Supplementary proline may possibly lessen the progression of chorioretinal lesions in gyrate atrophy.